"Fear of the unknown": Health, disability, and stakeholder perspectives on the behavioral and social drivers of vaccination in children with disability in Fiji. - Rosalie Power; Unise Vakaloloma; Israt Jahan; Sureni Perera; Ilisapeci Tuibeqa; Rachel Devi; Litiana Volavola; William May; Donald Wilson; Lanieta Tuimabu; Gulam Khandaker; Meru Sheel; et al. (PLOS Global Public Health)
Vaccinating children with disability in low- and middle-income countries, such as Fiji, is a key priority for equity. This study aimed to understand the social and behavioral drivers of vaccine uptake among children with disability in Fiji, from the perspectives of health, disability, and community stakeholders. Five qualitative focus groups were conducted with 22 stakeholders, including healthcare workers, disability service providers and advocates, and community and faith leaders (female n = 17, 77%). Data were collected and analyzed using reflexive thematic analysis and applied the World Health Organization's Behavioral and Social Drivers of Vaccination framework. Numerous drivers were reported to impact vaccination for children with disability. These included (1) Thinking and feeling: lack of reliable information about vaccine benefits and safety for children with disability; (2) Social processes: disability stigma and discrimination impacted families of children with disability engaging with healthcare services; lack of tailored vaccination communication and engagement strategies; and, need for improved disability and health service collaboration; (3) Motivation: lack of awareness and support for parents of children with disability to have their children vaccinated, and religious beliefs negatively impacted motivation; (4) Practical issues: long waiting times and lack of suitable waiting areas for children with disability; financial and time barriers; and, lack of healthcare worker knowledge and confidence in providing vaccines to children with disability, impacted patient-provider trust. The findings from this study can inform strategic actions to overcome barriers to vaccination for children with disability, including strengthening existing vaccination programs, promoting greater equity in vaccination for children with disability in Fiji. This will reduce the burden of vaccine-preventable diseases in this priority group.